2018
DOI: 10.1002/jez.2188
|View full text |Cite
|
Sign up to set email alerts
|

Colors of attraction: Modeling insect flight to light behavior

Abstract: Light sources attract nocturnal flying insects, but some lamps attract more insects than others. The relation between the properties of a light source and the number of attracted insects is, however, poorly understood. We developed a model to quantify the attractiveness of light sources based on the spectral output. This model is fitted using data from field experiments that compare a large number of different light sources. We validated this model using two additional datasets, one for all insects and one exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 42 publications
0
68
1
Order By: Relevance
“…Studies on the phototactic behavior of insects towards LED lights of specific wavelengths are in progress and light traps using LED lights with specific wavelengths can be used to monitor and manage agricultural and forest pest populations as a means of physical pest control in a future IPM strategy …”
Section: Considerable Problems In the Application Of Light Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the phototactic behavior of insects towards LED lights of specific wavelengths are in progress and light traps using LED lights with specific wavelengths can be used to monitor and manage agricultural and forest pest populations as a means of physical pest control in a future IPM strategy …”
Section: Considerable Problems In the Application Of Light Trapsmentioning
confidence: 99%
“…Light source wavelengths should also be screened for those that are effective at attracting pests, while having little negative influence on the growth of crops …”
Section: Considerable Problems In the Application Of Light Trapsmentioning
confidence: 99%
“…Exposure to blue light at night is known to cause insomnia and increased disease risk in humans (American Medical Association, ). However, the effects of this widespread spectral shift on other organisms have only recently attracted the attention of researchers (Davies et al, ; Donners et al, ; Gaston, Visser, & Hölker, ; Justice & Justice, ; Lewanzik & Voigt, ; Longcore et al, ; Pawson & Bader, ; Plummer, Hale, O'Callaghan, Sadler, & Siriwardena, ; Somers‐Yeates, Hodgson, McGregor, Spalding, & Ffrench‐Constant, ; Spoelstra et al, ; van Grunsven et al, ; van Langevelde, Grunsven, Veenendaal, & Fijen, ; Wakefield, Broyles, Stone, Jones, & Harris, ).…”
Section: Introductionmentioning
confidence: 99%
“…Donners et al . () and Longcore et al . () have devised theoretical models to determine how specific light sources overlap with the full range of visual sensitivities for organisms.…”
Section: Introductionmentioning
confidence: 88%
“…Although numerous studies have investigated behavioral responses to different light sources (Langevelde et al, 2011;van Grunsven et al, 2014;Longcore et al, 2015;Spoelstra et al, 2017), few studies have investigated varied spectral signatures in the environment, see Davies et al (2013); Donners et al (2018); Longcore et al (2018). Davies et al (2013) found that low-pressure sodium lamps emitted the smallest proportion of the light spectrum to which animals are sensitive, whereas metal halides (MH) lamps emitted the largest proportion.…”
Section: Introductionmentioning
confidence: 99%